Simulation of forming diffusion zone at impulse electron-beam treatment of coated material; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Bukrina N. V. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа